Hardware para potenciales evocados visuales y señales de RF (2016)
This document shows the validation of a system that emulates radio frequencies (RF) and at the same time allows the visual stimulation to generate visual evoked potentials (VEPs). This system is implemented for the study of RF waves effect in the human brain. Therefore, the tests performed in this paper are directed towards identifying relevant parameters, such as band width, central frequency, and power transmission. Referring to visual stimulation, the validation was made following the ISCEV standard for VEPs. Finally, the validation results, the identified system?s failures, and the suggested alternatives to implement the appropriate improvements are shown.